Software representation methodology for agile application development: An architectural approach - Alejandro Paolo Daza Corredor; John Freddy Parra Peña; Lilia Marcela Espinosa Rodriguez (Redes de Ingeniería, 2016)
The generation of Web applications represents the execution of repetitive tasks, this process involves determining information structures, the generation of different types of components and finally deployment tasks and tuning applications. In many applications of this type are coincident components generated from application to application. Current trends in software engineering as MDE, MDA or MDD pretend to automate the generation of applications based on structuring a model to apply transformations to the achievement of the application. This document intends to translate an architectural foundation that facilitates the generation of these applications relying on model-driven architecture but without ignoring the existence and relevance of existing trends mentioned in this summary architectural models.